STRATEGI KOMUNIKASI ISLAM DALAM MODERASI BERAGAMA DAN PEDULI LINGKUNGAN SOSIAL DI DESA RAYA - Isran Rasyid Karo-Karo; Mahathir Muhammad Hutasuhut; Alfiansyah Borotan; Dwi Andini; Nurmawaty Hasugian; Siska Amelia (Program Studi Komunikasi dan Penyiaran Islam, 2026)
Islamic communication plays an important role in fostering harmony and addressing socio-ecological challenges in plural societies. This study aims to describe Islamic communication strategies in strengthening religious moderation and social-environmental awareness in Desa Raya, Berastagi District, Karo Regency. This research employed a qualitative descriptive approach, with data collected through participatory observation, in-depth interviews, and documentation of community engagement activities carried out by students. Data analysis followed Miles & Huberman’s interactive model, including data reduction, display, and conclusion drawing. The findings reveal that Islamic communication strategies for religious moderation were implemented through educational seminars, interfaith tolerance declarations, joint prayers, and tree planting as a symbol of unity. Meanwhile, social-environmental awareness was fostered through eco-brick education, installation of waste disposal signs, community clean-ups, elderly exercise, as well as religious services and children’s education. The integration of both aspects occurred through dakwah bil hal, which combined persuasive, symbolic, and participatory messages. The study concludes that Islamic communication in Desa Raya was not limited to verbal preaching but was embodied in concrete actions that strengthened interfaith harmony while raising ecological awareness within the community